2014
DOI: 10.3758/s13415-013-0243-x
|View full text |Cite
|
Sign up to set email alerts
|

Can we shield ourselves from task disturbance by emotion-laden stimulation?

Abstract: Emotion-laden stimuli can disturb information processing in an unrelated cognitive task. We investigated the possibilities and limitations for shielding from such disturbance. Participants performed a simple categorization task while being simultaneously exposed to negative, neutral, and positive pictures. Performance dropped with negative pictures, relative to positive and neutral stimuli. Unlike Stroop or Simon interference effects, this negativity-based disturbance did not reduce as a function of previous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 74 publications
2
18
1
Order By: Relevance
“…Did they observe similar findings as in this study? Augst, Kleinsorge, and Kunde (2014), who also used a spatial attention task, showed that announcing the emotional content of an upcoming distractor did not decrease emotional interference of such a distractor (Experiment 3). Similar findings were observed in a recent study by Dieterich, Endrass, Kathmann, and Weinberg (2019) that examined behavioral interference and the LPP for aversive and neutral distractors when participants were informed of their specific content (predictable condition) or were not informed (unpredictable).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Did they observe similar findings as in this study? Augst, Kleinsorge, and Kunde (2014), who also used a spatial attention task, showed that announcing the emotional content of an upcoming distractor did not decrease emotional interference of such a distractor (Experiment 3). Similar findings were observed in a recent study by Dieterich, Endrass, Kathmann, and Weinberg (2019) that examined behavioral interference and the LPP for aversive and neutral distractors when participants were informed of their specific content (predictable condition) or were not informed (unpredictable).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the findings from previous studies indicate that providing participants with explicit information about the specific emotional content of the distractors does not reduce emotional interference, whereas the high frequency of distractors in the present studies prompted a consistent attenuation. A possible explanation may rely on the fact that these previous studies compared two conditions in which distractors were always expected (Dieterich et al, 2019;Augst et al, 2014), and only the content could be uncertain, whereas in these studies, we compared a condition where distractors were rare and unexpected with a condition where they were frequently presented. Therefore, distractor frequency and explicit cueing (announcing the emotional content of an upcoming distractor) seem to engage different top-down mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a word, negative stimuli, regardless of whether the stimuli inherently high or low motivational intensity have, convey crucial information meaning that the organism should escape from the current environment or adjust actions. Thus, both high-and low-withdrawal motivation negative stimuli require attentional resources for the prioritized processing of these stimuli and thus delay the processing of a goal task (Augst et al, 2014). Once a stimulus captures one's attention, we should then disengage from this stimulus and begin to process the next stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Across experiments Augst et al (2014) found that negative emotional distractors were more potent than neutral and positive distractors, even in the proactive control conditions. However, this cannot be interpreted as evidence that emotional attention is independent of top-down control because the results also suggest that they did not successfully engage proactive control with their manipulations.…”
Section: Empirical Evidence: Can Emotional Stimuli Be Effectively Controlled?mentioning
confidence: 88%
“…In many cases emotion is an irrelevant property of an attended object either because it is the target (as, for example, in the emotional Stroop task; see Phaf & Kan, 2007 for a meta-analysis; see Williams et al, 1996 for a review), or because it could be the target (as, for example, in variants of the visual search task in which the emotionality of distractors in the array is manipulated; e.g., Hodsoll, Viding & Lavie, 2011;Lipp & Waters, 2007;Miltner, Krieschel, Hecht, Trippe & Weiss, 2004). In other studies, emotional distractors are distinct from the target stimulus, but are presented in attended spatial locationseither because they are presented in the same location as targets (e.g., Attar & Müller, 2012;Haas, Omura, Constable & Canli, 2006Sussman, Heller, Miller & Mohanty, 2013), or at fixation (e.g., Augst, Kleinsorge & Kunde, 2014;Erthal et al, 2005;Fernandes, Koji, Dixon & Aquino, 2011) which is an inherently attended location (see Beck & Lavie, 2005). When distractors are relevant, or share properties with relevant information (i.e., are a property of an attended object, or are presented in an attended location), there is robust evidence that emotional information is more distracting than neutral information.…”
Section: Emotional Distractionmentioning
confidence: 99%